Quality-controlled datasets of Automatic Weather Station (AWS) at SIGMA-A site from 2012 to 2020: Level 1.3 ... - Nishimura, Motoshi; Aoki, Teruo; Niwano, Masashi; Matoba, Sumito; Tanikawa, Tomonori; Yamaguchi, Satoru; Yamasaki, Tetsuhide; Tsushima, Akane; Fujita, Koji; Iizuka, Yoshinori; Kurosaki, Yutaka (Arctic Data archive System (ADS), Japan, 2023)
Time-series data of an automatic weather station (AWS) operated at the SIGMA-A site on the Greenland ice sheet since June 2012. The AWS measures the meteorological parameters every hour, which are air temperature, relative humidity, wind speed, wind direction, atmospheric pressure, shortwave radiation, longwave radiation, near-infrared radiation, snow height, and snow temperature. This dataset (data level: 1.3) has been completed data masking procedures to eliminate all erroneous data records. Detailed information of the data level definition and versions are referred to "readme_SIGMA-A_Level_1.3.txt". It is strongly recommended to refer to "Dataset Revision Record" in the readme file and use the latest version of the dataset. ...